Socio demographic and basic living characteristics in relation to development and change in Nepal based on Nepal Living standard Survey 2022/2023 data - Sapkota, Bhesh Nath (Rural Development Journal, 2026)
The V shaped curve is obtaining in Nepal while decreasing age from lower to higher age group which is indicator of constant increase mortality. Almost all population are dying between 60-79 years is worst indicator of development and change process. It indicated that the health condition of adults and old population is worst compared with infant and children. Age-sex distribution are basic population characteristics and indicator of development and change. In this article the 95 per cent confidence interval technique has used with “population adjusted” with population census 2021 data to analyzed Nepal Living Standard Survey data 2022/23 by Python 3.12 tools. The narrow confidence interval indicated precise methodology chosen while designing and conducting survey. More than 5 per cent households has not any type of toilet in Nepal still today.